The usefulness of the bioconcentration factor as a tool for priority setting in chemicals control - Nordberg, Anna; Rudén, Christina (Toxicology letters, 2007)
The implementation of the REACH system will lead to the creation of a single, uniform legislation for industrial chemicals in Europe. An important aim of this legislation is to generate toxicity data for previously untested chemicals. Testing tens of thousands of chemicals can however not be done in one step, and criteria for priority setting is therefore an essential part of the proposed REACH system. In this study we investigate potential consequences of using bioaccumulation (B) data as a tool for priority setting in chemicals control. The results of this investigation suggests that the use of data for the bioconcentration factor (BCF, as an estimation of B) at first tier will not introduce bias towards a particular type of toxicity (i.e. carcinogenicity, reproductive toxicity or mutagenicity) in the priority setting process.